Estado nutricional dos pré-escolares matriculados em creches do município de Franca-SP no ano de 2009 - Ferro, Élen Lúca Bagatini Saud (2010)
With an increasing participation of women in the labor market, there is a need for institutions where mothers can leave their children while away from home. Such role is performed by daycare centers and preschools that are also responsible for feeding children during their stay. The responsibility of these places on the nutritional status of these children is big. This research was designed to evaluate the nutritional status of preschool children enrolled in 24 daycare centers in the city of Franca - São Paulo in 2009 and relate it to the characteristics of food they provide. The total population analyzed in this cross-sectional study conducted during the year 2009 was 694 children, whose weight and height was measured to calculate their BMI (Body Mass Index), which was applied to the new growth curves of the WHO (2006-2007) and classified according to the parameters set by the WHO (2006), and triceps and subscapular skinfolds, whose sum followed the pattern of the NCHS (1976-1980) and the classification of Frisancho (1990). The characteristics of daycare centers were obtained through a questionnaire applied to the directors. The results showed a rate of 69.3% for eutrophic, 14% for risk of overweight, 6.5 for overweight, 3.5% for obesity, 6.1% for underweight and 0.7 for severe underweight. In daycare centers, where meals were provided through the self service system with the help of teachers and cooks, the average of overweight was 39.7%. The lower incidence of overweight (6.7%) was found in an orphanage that followed a vegetarian menu. Regarding skinfolds, 11% of children were found with low-fat, 66.5% were normal and 22.5% were higher than the expected for body adiposity. These results demonstrate that the monitoring of infant feeding should begin as early as possible in order to prevent future harm to their health.